Discovery of mitochondrial DNA variants associated with genome-wide blood cell gene expression: a population-based mtDNA sequencing study - Jaakko Laaksonen; Ilkka Seppälä; Emma Raitoharju; Nina Mononen; Leo-Pekka Lyytikäinen; Melanie Waldenberger; Thomas Illig; Maija Lepistö; Henrikki Almusa; Pekka Ellonen; Nina Hutri-Kähönen; Markus Juonala; et al. (OXFORD UNIV PRESS, 2022)
The effect of mitochondrial DNA (mtDNA) variation on peripheral blood transcriptomics in health and disease is not fully known. Sex-specific mitochondrially controlled gene expression patterns have been shown in Drosophila melanogaster but in humans, evidence is lacking. Functional variation in mtDNA may also have a role in the development of type 2 diabetes and its precursor state, i. e. prediabetes. We examined the associations between mitochondrial single-nucleotide polymorphisms (mtSNPs) and peripheral blood transcriptomics with a focus on sex-and prediabetes-specific effects. The genome-wide blood cell expression data of 19 637 probes, 199 deep-sequenced mtSNPs and nine haplogroups of 955 individuals from a population-based Young Finns Study cohort were used. Significant associations were identified with linear regression and analysis of covariance. The effects of sex and prediabetes on the associations between gene expression and mtSNPs were studied using random-effect meta-analysis. Our analysis identified 53 significant expression probe-mtSNP associations after Bonferroni correction, involving 7 genes and 31 mtSNPs. Eight probe-mtSNP signals remained independent after conditional analysis. In addition, five genes showed differential expression between haplogroups. The meta-analysis did not show any significant differences in linear model effect sizes between males and females but identified the association between the OASL gene and mtSNP C16294T to show prediabetes-specific effects. This study pinpoints new independent mtSNPs associated with peripheral blood transcriptomics and replicates six previously reported associations, providing further evidence of the mitochondrial genetic control of blood cell gene expression. In addition, we present evidence that prediabetes might lead to perturbations in mitochondrial control.